2006
DOI: 10.1086/497952
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen from the λ7774 High‐Excitation Triplet in Open Cluster Dwarfs: Hyades

Abstract: Oxygen abundances have been derived from the near-IR, high-excitation O i k7774 triplet in high-resolution, high signal-to-noise ratio spectra of 45 Hyades dwarfs using standard one-dimensional, plane-parallel LTE models. Effective temperatures of the stellar sample range from 4319 to 6301 K, and the derived relative O abundances as a function of T eff evince a trichotomous morphology. At T eA > 6100 K, there is evidence of an increase in the O abundances with increasing T eff , consistent with non-LTE (NLTE) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 42 publications
10
70
0
Order By: Relevance
“…We present here a comparison of our results with selected previous analyses of Hyades stars: Paulson et al (2003), Schuler et al (2006) and Carrera & Pancino (2011). These works were chosen because they have a larger number of stars in common with our analysis.…”
Section: Comparison With Other Workmentioning
confidence: 82%
See 2 more Smart Citations
“…We present here a comparison of our results with selected previous analyses of Hyades stars: Paulson et al (2003), Schuler et al (2006) and Carrera & Pancino (2011). These works were chosen because they have a larger number of stars in common with our analysis.…”
Section: Comparison With Other Workmentioning
confidence: 82%
“…Spectroscopic studies of FGK-type dwarfs in the Hyades find a metallicity of about +0.13 dex (Cayrel et al 1985;Boesgaard & Friel 1990;Paulson et al 2003;Schuler et al 2006). Regarding the giants, the metallicity values range from +0.10 up to +0.20 dex, where this scatter is usually attributed to the star HIP 20455, a spectroscopic binary (Schuler et al 2006;Carrera & Pancino 2011).…”
Section: Hyades: the Benchmark Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors do not generally agree whether this offset is due to NLTE effects in cool stars, in the sense that for stars with T eff ∼ 5000 K the offsets are large, while for T eff ∼ 6000 K good agreement is found (Ramírez et al 2007); this discrepancy is revealed in this case either by a disagreement between chemical abundances derived from different lines of the same species (atomic or molecular) or by the non-realization of the Fe i/Fe ii ionization equilibrium. Another interpretation is the presence of high chromospheric activity, an enhanced non-local UV radiation field, and a resulting photospheric overionization (Schuler et al 2006). In a classical spectroscopic analysis, forcing agreement between Fe i and Fe ii abundances under LTE, but in the presence of an overionizing radiation field, leads naturally to a higher T eff .…”
Section: Systematic Offset Between Photometric Hα and Spectroscopicmentioning
confidence: 99%
“…A long-standing problem in astrophysics stems from the work of Yong et al (2004) and Schuler et al (2004Schuler et al ( , 2006, who noticed startling discrepancies involving iron and oxygen abundances, leading to questions regarding the viability of standard 1D-LTE model atmospheres. Yong et al (2004) noticed that the overall iron abundance as inferred from the measurement of singly ionized iron lines rapidly increased in Hyades stars with decreasing T eff , starting at around 5000 K. Schuler et al (2006), likewise, found a similar trend with the inferred oxygen abundance from their measurements of the O I 777 nm triplet lines in dwarf stars of the Hyades, Pleiades, and M34 open clusters.…”
Section: Introductionmentioning
confidence: 99%